The axiological and cultural-logical approaches to the professional training of future teachers of physical training for the physical-cultural-healing work at the high school - Konovalska, Lyudmila (Berdyansk State Pedagogical University, 2018)
The article deals with the analysis of the axiological and cultural-logical approaches to the professional training of future teachers of physical culture as the leading within the modernization of the high physical-cultural education. It is revealed the meaning of these approaches within the process of the professional training of future teachers of physical culture for the physical-cultural healing work at high school.
Keywords: axiological approach; cultural-logical approach; value; principles; future teacher of the physical culture